A situation analysis of street children in Harare, Zimbabwe - Pascoe, Margaret Joy (Department of Paediatrics and Child Health, 2017)
The problem of children on the streets of Harare has been increasing over the last five years. The majority of these children appear to be of school-going age. Who are these children? Where do they live? Why are they not attending school? This study is an attempt to provide answers for these questions, to evaluate current policy and programmes for street children and to promote appropriate and effective policy measures. A convenience sample of two hundred and eight children, who fulfilled the definition of street child used in the study, were interviewed using a questionnaire and focus group discussions. A number of children's homes, a probation centre and a remand home were visited and personnel from non-governmental organisations working with street children were interviewed. The study found that the majority of children were male (89%), and the age distribution ranged from six to seventeen years. The mean time period spent on the street was 18,4 months. The most common reason for leaving home was that the family was unable to support the child. Most of the children slept in a nearby squatter settlement or at the city railway station. The most popular income generating activity was guarding motor vehicles. Five of the children were attending alternative education programmes and one third had never attended school. The most common medical conditions were acute respiratory infections, diarrhoeal disease and skin rashes. Some of the children had suffered physical (12) and /or sexual (10) abuse while on the street. Substance abuse, notably glue sniffing, was widespread with 78% of the children admitting to this activity. A general attitude of hopelessness prevailed among the children and few could envisage brighter prospects for the future. Short term measures to improve the children's lives on the street must be taken, but the long-term solution requires a broad attack on poverty in order to eradicate the root problems that force children onto the streets. Recommendation were aimed at the major role players in the lives of street children - the Government, the Department of Social Welfare, the Zimbabwe Republic Police and Non-Governmental Organisations.